Optimalisasi Pengisian Accu Pada Sistem Pembangkit Listrik Tenaga Surya (PLTS) Dengan Solar Charge Controller (MPPT) - Muhammad Suyanto; Sigit Priyambodo; Prasetyono E.P; Ari Purnama Aji (Jurnal Teknologi, 2022)
The use of renewable energy is currently one of the alternative energies to support the decline in fossil energy in Indonesia. Solar energy is the right choice for now, as a solar power plant (PLTS), which is a renewable technology, which can convert solar thermal energy into electrical energy. The solar power generation system has various components, one of which is the Solar charge controller. The purpose of this research is to optimize battery charging using the MPPT Solar charge controller type. MPPT solar charge controller, has better characteristics and is able to charge the battery (accu) faster. In this study also pay attention to the effect of light intensity and temperature on the power output generated by the solar cell. The results showed that the MPPT Solar charge controller was able to work better and faster in charging the battery (accu) than other Solar charge controllers. It is proven by the results of the average voltage, current and output power of the MPPT controller of 13.79 volts, 3.06 amperes and 42.26 watts of power, for high light intensity and temperature do not always affect the results of high voltage, current and power, because environmental factors also affect the output of the solar cell.